PENERAPAN SOSIAL MEDIA MARKETING DAN LAPORAN KEUANGAN GUNA MENGEMBANGKAN BISNIS KAFE LOE-KITA - Phandy, Angelina; Ivana Yosal, Calista; Brilianti Wilar, Felicia; Tony Putri, Telysia; Sharon, St Salmah (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2026)
This article discusses implementing the Social Innovation Challenge (SIC) Program in partnership with Kafe Loe Kita in Makassar, focusing on improving digital marketing capabilities and preparing financial reports for MSMEs. The program addresses the problems of partners who have not optimally utilized social media as a promotional tool and do not yet have a structured financial reporting system. Activities are carried out through direct training at partner locations using a practical approach (learning by doing) that includes creating creative content on Instagram, using paid promotion features, and preparing financial reports such as balance sheets, profit and loss, and cash flow. The results of the activities showed an increase in the digital marketing aspect, marked by an increase in Instagram followers from 0 to 1,081 in three weeks, and content reach reaching more than 11,000 accounts. On the financial side, cafe staff were able to prepare reports independently, even though there were minor errors in the classification of production costs, which remained within the error tolerance threshold of 5%. This program proves that the combination of effective digital marketing strategies and systematic financial management can increase the competitiveness and operational efficiency of MSMEs. The success of the implementation of this program also has the potential to be replicated in similar businesses as an empowerment model based on educational collaboration and business practices. — Artikel ini membahas pelaksanaan Program Social Innovation Challenge (SIC) yang bermitra dengan Kafe Loe Kita di Makassar, dengan fokus pada peningkatan kemampuan pemasaran digital dan penyusunan laporan keuangan UMKM. Program dirancang untuk mengatasi permasalahan mitra yang belum optimal dalam pemanfaatan media sosial sebagai alat promosi serta belum memiliki sistem pelaporan keuangan yang terstruktur. Kegiatan dilakukan melalui pelatihan langsung di lokasi mitra menggunakan pendekatan praktik (learning by doing) yang mencakup pembuatan konten kreatif di Instagram, penggunaan fitur promosi berbayar, dan penyusunan laporan keuangan seperti neraca, laba rugi, dan arus kas. Hasil kegiatan menunjukkan peningkatan dalam aspek pemasaran digital, ditandai dengan bertambahnya pengikut Instagram dari 0 menjadi 1.081 dalam tiga minggu, serta jangkauan konten mencapai lebih dari 11.000 akun. Di sisi keuangan, staf kafe mampu menyusun laporan secara mandiri meskipun terdapat kesalahan minor dalam klasifikasi biaya produksi, yang tetap berada dalam ambang toleransi kesalahan sebesar 5%. Program ini membuktikan bahwa kombinasi antara strategi digital marketing yang efektif dan pengelolaan keuangan yang sistematis dapat meningkatkan daya saing dan efisiensi operasional Kafe Loe Kita. Keberhasilan pelaksanaan program ini juga berpotensi untuk direplikasi pada usaha sejenis sebagai model pemberdayaan berbasis kolaborasi pendidikan dan praktik bisnis.